CCR5 as a Coreceptor for Human Immunodeficiency Virus and Simian Immunodeficiency Viruses: A Prototypic Love-Hate Affair - Jasinska, Anna J.; Pandrea, Ivona; Apetrei, Cristian (Frontiers in Immunology, 2022)
CCR5, a chemokine receptor central for orchestrating lymphocyte/cell migration to the sites of inflammation and to the immunosurveillance, is involved in the pathogenesis of a wide spectrum of health conditions, including inflammatory diseases, viral infections, cancers and autoimmune diseases. CCR5 is also the primary coreceptor for the human immunodeficiency viruses (HIVs), supporting its entry into CD4+ T lymphocytes upon transmission and in the early stages of infection in humans. A natural loss-of-function mutation CCR5-Δ32, preventing the mutated protein expression on the cell surface, renders homozygous carriers of the null allele resistant to HIV-1 infection. This phenomenon was leveraged in the development of therapies and cure strategies for AIDS. Meanwhile, over 40 African nonhuman primate species are long-term hosts of simian immunodeficiency virus (SIV), an ancestral family of viruses that give rise to the pandemic CCR5 (R5)-tropic HIV-1. Many natural hosts typically do not progress to immunodeficiency upon the SIV infection. They have developed various strategies to minimize the SIV-related pathogenesis and disease progression, including an array of mechanisms employing modulation of the CCR5 receptor activity: (i) deletion mutations abrogating the CCR5 surface expression and conferring resistance to infection in null homozygotes; (ii) downregulation of CCR5 expression on CD4+ T cells, particularly memory cells and cells at the mucosal sites, preventing SIV from infecting and killing cells important for the maintenance of immune homeostasis, (iii) delayed onset of CCR5 expression on the CD4+ T cells during ontogenetic development that protects the offspring from vertical transmission of the virus. These host adaptations, aimed at lowering the availability of target CCR5+ CD4+ T cells through CCR5 downregulation, were countered by SIV, which evolved to alter the entry coreceptor usage toward infecting different CD4+ T-cell subpopulations that support viral replication yet without disruption of host immune homeostasis. These natural strategies against SIV/HIV-1 infection, involving control of CCR5 function, inspired therapeutic approaches against HIV-1 disease, employing CCR5 coreceptor blocking as well as gene editing and silencing of CCR5. Given the pleiotropic role of CCR5 in health beyond immune disease, the precision as well as costs and benefits of such interventions needs to be carefully considered.